Problem Pendidikan Anak Tenaga Kerja Wanita Indonesia (TKWI) di Desa Keruak Kecamatan Keruak Kabupaten Lombok Timur - Jamiluddin Jamiluddin (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2017)
This study aims to determine the child's education problems Indonesia Labor Women (TKWI). The type used in this research is qualitative descriptive exploratory approach. In the process of data collection researchers using participant observation, interview methods (interviews), and methods of documentation. Nurturing and raising children is a responsibility that must be carried naturally by the parents, because the child needs food, drinks, and respite care so that he can live in a sustainable manner and also be able to enjoy a decent school with. Making the role of the mother by the father, brother or grandmother has not been able to make the development of children walking normally like other children who grew up with the supervision, guidance and get a touch of affection directly a mother, which eventually resulted in not a few of the children who left the mother becomes TKW their performance declines, one of the association, even dropouts.